Penanganan Aset Kripto Sebagai Barang Bukti Dalam Perkara Pidana - Muh. Ibnu Fajar; Desty Puspita Sari (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
The increasing number of users and transactions of crypto assets every year has the potential to increase the modus operandi of criminal acts that use crypto assets, either as a tool to commit a criminal act (instrumental offense) or as a result of a criminal act (corpus delicten). Crypto assets are evidence that are very vulnerable, fluctuating in value, and easily changed and transferred. Therefore, handling must be done quickly and precisely. Handling of crypto assets must comply with the exclusionary of rule principle which requires obtaining evidence in ways that are based on law so that crypto assets become legal evidence (lawfully legal evidence) to be used in proving criminal cases. The prosecutor as case controller (dominus litis) has the responsibility to maintain the integrity of crypto assets as evidence and/or valid evidence, both at the stages of investigation, prosecution, examination at trial, and implementation of court decisions. In practice, there is no legal instrument that specifically regulates procedures for handling crypto assets in criminal cases, giving rise to different handling practices (disparities). Therefore, a common perception is needed regarding the handling of crypto assets as evidence in criminal cases.